Determination of Lead and Cadmium Levels in Local and Imported Carrots and Cabbage (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted on the determination of levels of lead and cadmium in some samples of cabbage and carrots .which was collected from the markets and the most crowded people in the Najaf city of 2017,using an atomic absorption spectrometer.                                                                                                                     Results showed lead accumulation in some samples the highest concentration was in the Iranian green cabbage (1.478)part per million and the green cabbage of Iraqi (1.344) part per million, while the lowest concentration was in the Iraqi orange carrots (0.201) part per million.                                                                        Results of cadmium concentration in all samples, the highest concentration were in Iranian cabbage (0.047) part per million and Iranian green cabbage (0.046) part per million, the lowest value in the Iraqi violet carrots (0.035) part per million and the Iraqi yellow carrots (0.040) part per million .                              A higher result indicates that there are metal accumulations of lead and cadmium in cabbage and carrot compared with permitted levels according to the World Health Standards because of the seriousness of these elements and harmful to human tissue for all these reasons ,this field study is important to determine the levels of elemental (lead and cadmium) in the cabbage and carrots produced locally and imported.